2022
DOI: 10.3389/fpls.2022.863467
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Pre-harvest Treatments Leads to Maintenance of Sweet Cherry Quality During Storage by Increasing Antioxidant Systems

Abstract: Melatonin has been reported to have an important role in fruit ripening, although the effect of pre-harvest melatonin treatment on sweet cherry quality properties during storage is still unknown. In the present experiments, the effects of melatonin (0.1, 0.3, and 0.5 Mm) by foliar spray treatments of ‘Prime Giant’ and ‘Sweet Heart’ sweet cherry trees on fruit quality traits and antioxidants systems during storage was evaluated. Results showed that these treatments reduced weight losses during storage, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 57 publications
(105 reference statements)
7
23
0
1
Order By: Relevance
“…Sweet cherry quality is evaluated through its physicochemical parameters and evolution throughout its commercial life or shelf life. Losses in weight, firmness and titratable acidity during storage and subsequent shipment, along with changes in skin colour and total soluble solids content, define their quality and consumer acceptance as well as their repurchase [ 32 ]. Once harvested, they begin to undergo physiological changes that cause rapid deterioration of the fruit, and consequently, cherries that reach consumers may not have the optimal organoleptic characteristics [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sweet cherry quality is evaluated through its physicochemical parameters and evolution throughout its commercial life or shelf life. Losses in weight, firmness and titratable acidity during storage and subsequent shipment, along with changes in skin colour and total soluble solids content, define their quality and consumer acceptance as well as their repurchase [ 32 ]. Once harvested, they begin to undergo physiological changes that cause rapid deterioration of the fruit, and consequently, cherries that reach consumers may not have the optimal organoleptic characteristics [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the enzymes peroxidase (POD), catalase (CAT) and ascorbate peroxidase (APX) was measured as described by Carrión-Antoli et al [ 32 ]. Briefly, 5 g homogenate was mixed with 10 mL of 50 mM phosphate buffer, pH = 7.0, containing 1% ( p/v ) polyvinylpyrrolidone and 1 mM ethylenediaminetetraacetic acid.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, SOD is the only enzyme in plant cells with the disproportionation ability to dismutate superoxide anions into H 2 O 2 and H 2 O ( Serna-Escolano et al., 2021 ; Mitalo et al., 2022 ). Then, CAT and POD are two important antioxidant enzymes that act synergistically to decompose the produced H 2 O 2 into H 2 O and O 2 , thus reducing the harmful effect of over-produced H 2 O 2 in plant cells ( Carrión-Antolí et al., 2022 ; Hanaei et al., 2022 ; Nxumalo et al., 2022 ). At the same time, APX and GR, as the key enzymes in AsA-GSH system, have a crucial part in maintaining redox homeostasis and protecting plant cells form excess ROS-incited oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…CAT (EC 1.11.1.6) activity was determined according to the method of Carrión-Antolí et al. (2022) in the presence of H 2 O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that hormones, such as ET, SA, gibberellins [GAs, including gibberellin 1 (GA1), gibberellin 3 (GA3), gibberellin 4 (GA4), and gibberellin 7 (GA7)], MeJA, and abscisic acid (ABA), modulate the postharvest preservation of fruits and vegetables (70,(74)(75)(76)(77). Over the past several years, numerous reports have proposed that melatonin acts as an important role on qualities of fruits and vegetables during the postharvest period (53, 54, 56-60, 67, 76).…”
Section: Protective Effects Of Exogenous Melatonin On Qualities Of Fr...mentioning
confidence: 99%